Trade union investment companies: promoting worker control and a solidarity economy in South Africa? - Manjonjo, Kudakwashe Andrew (My University, 2021)
This research looks into the extent of which the concepts and practises worker control and the solidarity economy are present in two South African Trade Union Investment Companies, namely Hosken Consolidated Investments (owned by the South Africa Clothing and Textiles Workers Union) as well as the Mining Investment Company (owned by National Union of Mineworkers). Theoretically, the research looks at how the theories of Labour Process Theory, hegemony and counter hegemony can aid understand the role TUICs can play for trade unions. This is accompanied by perusing through literature relating to financialization, trade unionism as well as the solidarity economy. The research used qualitative research to investigate and analyse the two studies anchored on interviews and secondary documentary research. The research results are that there is little worker control or dedication to the solidarity economy within the case studies. Regarding worker control, the arm’s length governance systems, weak union-investment company mechanisms, labour aristocracy, secondary emphasis on cooperatives, managerial employee share ownership schemes and the principle of “invest where you do not organize” have negatively impacted on worker control over the investment companies. Regarding the solidarity economy, the emphasis on corporate social responsibility, casino capitalism, high debt structures, the Black Economic Empowerment Programme as well as a continued commitment to fossil fuel investments have limited the solidarity economy. However, there is room and practise in place that provide opportunity for the investment companies to increase worker control and improve on the solidarity economy practises.
A dissertation submitted in partial fulfilment of the requirements for the degree Master of Arts in Labour Policy and Globalization to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021